Potassium Sulfate Spray Promotes Fruit Color Preference via Regulation of Pigment Profile in Litchi Pericarp - Su, Xuexia; Bai, Cuihua; Wang, Xianghe; Liu, Huilin; Zhu, Yongcong; Wei, Leping; Cui, Zixiao; Yao, Lixian (Frontiers in Plant Science, 2022)
Fruit color is a decisive factor for consumers’ preference. The bright red color of litchi fruit is associated with its high anthocyanin, however, poor fruit coloration is a major obstacle in litchi plantation. The role of spraying mineral nutrient salts including KH2PO4, KCl, K2SO4 and MgSO4 on litchi pericarp pigmentation was examined by a field trial, and the relation between human visual color preference versus pericarp pigments and hue-saturation-brightness (HSB) color parameters was investigated. K2SO4-sprayed litchi fruit gained the maximum popularity for its attractive red color. Spray of K and Mg salts decreased the buildup of yellowish pigments, but increased the accumulation of red ones, with the exception of slightly reduced anthocyanins in KH2PO4-sprayed fruit, by regulating the activities of enzymes involved in anthocyanidin metabolism and decreasing pericarp pH, leading to varied pericarp pigment composition. K2SO4 spray generated the highest percent of cyanidin-3-glucoside over all pigments in pericarp. Correlation analysis shows the percent of cyanidin-3-glucoside, superior to anthocyanin concentration and HSB color parameters, was a reliable indicator to fruit color preference. This work demonstrates that spray of suitable mineral salt can regulate pericarp pigment profile, and is an effective approach to improve fruit pigmentation and promote its popularity.